2009
DOI: 10.1007/s00701-009-0184-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multislice computed tomography angiography and digital subtraction angiography in the detection of residual or recurrent aneurysm after surgical clipping with titanium clips

Abstract: Using MDCTA, it is possible to demonstrate the status of intracranial aneurysms after surgical clipping in the immediate postoperative period as well as long-term follow-up with an high sensitivity and specificity when comparing with the findings of DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 10 publications
0
21
0
1
Order By: Relevance
“…In general practice with adequate clipping, often no follow-up imaging is performed, or it may be limited to immediate perioperative angiography. 156 In ISAT, there was a slightly higher risk of recurrent hemorrhage from a coiled aneurysm than from those treated with surgical clipping, but the risks in both groups were very small.…”
Section: Analysis and Reportingmentioning
confidence: 93%
“…In general practice with adequate clipping, often no follow-up imaging is performed, or it may be limited to immediate perioperative angiography. 156 In ISAT, there was a slightly higher risk of recurrent hemorrhage from a coiled aneurysm than from those treated with surgical clipping, but the risks in both groups were very small.…”
Section: Analysis and Reportingmentioning
confidence: 93%
“…CTA appears to be limited in detecting aneurysms less than 3 mm or when multiple clips were used [11]. Accuracy is also improved with the use of titanium clips and a multi-slice detector CTA [11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity, specificity, accuracy, positive predictive value and negative predictive value for CT angiography was achieved as 99, 99, 90, 96, and 98 by Westerlaan et al (17). Uysal et al reported the sensitivity and specificity of CT angiography in detecting aneurysm as 98.6 and 97.6, respectively (9).…”
Section: Discussionmentioning
confidence: 99%